Development of a Smartphone-Based Nanozyme-Linked Immunosorbent Assay for Quantitative Detection of SARS-CoV-2 Nucleocapsid Phosphoprotein in Blood - Liu, Bochao; Wu, Ze; Liang, Chaolan; Lu, Jinhui; Li, Jinfeng; Zhang, Ling; Li, Tingting; Zhao, Wei; Fu, Yongshui; Hou, Shuiping; Tang, Xi; Li, Chengyao (Frontiers in Microbiology, 2021)
Since December 2019, a novel coronavirus (SARS-CoV-2) has resulted in global pandemic of coronavirus disease (COVID-19). Although viral nucleic acid test (NAT) has been applied predominantly to detect SARS-CoV-2 RNA for confirmation diagnosis of COVID-19, an urgent need for alternative, rapid and sensitive immunoassays is required for primary screening of virus. In this study, we developed a smartphone based nanozyme linked immunosorbent assay (SP-NLISA) for detecting the specific nucleocapsid phosphoprotein (NP) of SARS-CoV-2 in 37 serum samples from 20 COVID-19 patients who were diagnosed by NAT previously. By using SP-NLISA, 28/37 (75.7%) serum samples were detected for NP antigen and no cross-reactivity with blood donors’ control samples collected from different areas of China. In a control assay with conventional ELISA, only 7/37 (18.91%) serum samples were detected for NP antigen and also no cross-reactivity with control samples. SP-NLISA could be used for rapid detection of SARS-CoV-2 NP antigen in primary screening of SARS-CoV-2 infected individuals.